Efektivitas Metode Gallery Walk Terhadap Peningkatan Keterampilan Berbicara Siswa pada Materi Teks Cerita Fiksi Kelas VII SMPN 1 Tirtajaya - Mulyadi, Oktapiani Astuti (Universitas Islam Sumatera Utara, 2025)
This study investigates the effectiveness of the Gallery Walk method in enhancing speaking skills among seventh-grade students at SMP Negeri 1 Tirtajaya during the 2023/2024 academic year, focusing on fictional narrative texts (fables). The research is driven by observed challenges, including students’ limited ability to express ideas orally, lack of innovative teaching strategies, and inefficient classroom time use. Employing a quantitative descriptive approach, this study utilizes a Pretest-Posttest Control Group Design conducted over four meetings. Participants consisted of class VII B (experimental group) and VII C (control group). Data were collected through interviews, questionnaires, and observations, and were analyzed using normality, homogeneity, and t-tests. Findings indicate that the Gallery Walk method significantly improves students’ speaking abilities in comparison to conventional methods. The average pretest score in the experimental group was 48.97, which increased to 79.38 in the posttest, with an N-Gain of 0.575, reflecting a moderate to high effectiveness level. The results suggest that this interactive, student-centered method promotes higher engagement and better oral performance. Hence, the Gallery Walk technique can serve as an effective pedagogical tool for fostering speaking proficiency in narrative learning contexts.